Drug Management Evaluation Focusing on Procurement at Muntilan District Hospital Magelang in Year 2015–2016 - Ulfah Mahdiyani; Chairun Wiedyaningsih; Dwi Endarti (Faculty of Pharmacy, Universitas Gadjah Mada)
Planning and procurement which are parts of management drug supply give the biggest effect on drug inventory and hospital’s cost. This study aimed to describe planning and procurement systems in Pharmacy Department of Muntilan Regional Public Hospital in year 2015–2016. Study was conducted by comparing the real drug management supply indicators with standard indicators. This study was conducted on December 2016 untill February 2017. Data was collected using retrospective approach for secondary data including data of finance, drug procurement and use; as well as primary data collected by interview with hospital director, and heads of pharmacy and finance department. Data was analyzed using descriptive technique. The result showed that drug management had not been fully in accordance with the standards. It was indicated from 7 measured indicators, one of them had been in accordance with the standard which was percentage of available fund compared with cost planned. The other 6 indicators had not been in accordance with the standard: percentage of drug procurement with fund allocation, percentage of drug item planned compared with the using, percentage total quantities of a drug item with the using, the procurement frequency of each drug item, frequency uncompleted of orderlist/contract, frequency of delayed rate in payment by hospital, and indicators that can’t be measured are proportion of the quantities of products actually recieved out of total quantities planned, and percentage of quantities used out of total quantities available for consumption after deduction of buffer stock.